A Role for Nrf2 Expression in Defining the Aging of Hippocampal Neural Stem Cells. Issue 4 (April 2018) - Ray, S.; Corenblum, M. J.; Anandhan, A.; Reed, A.; Ortiz, F. O.; Zhang, D. D.; Barnes, C. A.; Madhavan, L.
Redox mechanisms are emerging as essential to stem cell function given their capacity to influence a number of important signaling pathways governing stem cell survival and regenerative activity. In this context, our recent work identified the reduced expression of nuclear factor (erythroid-derived 2)-like 2, or Nrf2, in mediating the decline in subventricular zone neural stem progenitor cell (NSPC) regeneration during aging. Since Nrf2 is a major transcription factor at the heart of cellular redox regulation and homeostasis, the current study investigates the role that it may play in the aging of NSPCs that reside within the other major mammalian germinal niche located in the subgranular zone (SGZ) of the dentate gyrus (DG) of the hippocampus. Using rats from multiple aging stages ranging from newborn to old age, and aging Nrf2 knockout mice, we first determined that, in contrast with subventricular zone (SVZ) NSPCs, Nrf2 expression does not significantly affect overall DG NSPC viability with age. However, DG NSPCs resembled SVZ stem cells, in that Nrf2 expression controlled their proliferation and the balance of neuronal versus glial differentiation particularly in relation to a specific critical period during middle age. Also, importantly, this Nrf2-based control of NSPC regeneration was found to impact functional neurogenesis-related hippocampal behaviors, particularly in the Morris water maze and in pattern separation tasks. Furthermore, the enrichment of the hippocampal environment via the transplantation of Nrf2-overexpressing NSPCs was able to mitigate the age-related decline in DG stem cell regeneration during the critical middle-age period, and significantly improved pattern separation abilities. In summary, these results emphasize the importance of Nrf2 in DG NSPC regeneration, and support Nrf2 upregulation as a potential approach to advantageously modulate DG NSPC activity with age.